1990
DOI: 10.1002/j.1551-8833.1990.tb07056.x
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants in Polyelectrolytes Used in Water Treatment

Abstract: For approximately 30 years, the US Public Health Service and the US Environmental Protection Agency (USEPA) offered advisory opinions on the potential health effects of polyelectrolyte coagulant products used in drinking water treatment. In April 1990, the USEPA transferred this responsibility to a consortium of organizations led by the National Sanitation Foundation. Although more than 1,000 polyelectrolyte products were accepted for use by the USEPA, evidence suggests that probably fewer than 10 to 15 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…245, 230, and 220 nm in the interval 0.1 -4.0 mg/mL, 0.2 -3.0 mg/mL and 0.2 -6.0 mg/mL for samples 1, 2, and 3 respectively. The equations of calibration graphs and regression coefficients (R) for sample number 1, 2, and 3 are: [8][9][10]. We use the combination of MF and GPC to provide more complete information about the molecular weight distribution of the obtained fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…245, 230, and 220 nm in the interval 0.1 -4.0 mg/mL, 0.2 -3.0 mg/mL and 0.2 -6.0 mg/mL for samples 1, 2, and 3 respectively. The equations of calibration graphs and regression coefficients (R) for sample number 1, 2, and 3 are: [8][9][10]. We use the combination of MF and GPC to provide more complete information about the molecular weight distribution of the obtained fractions.…”
Section: Resultsmentioning
confidence: 99%
“…The normally used anionic and non-ionic polymers are low toxic, while cationic types are more toxic, especially for aquatic organisms [5,6]. The health significance of possible contaminants has been reviewed in detail [7,8]. Generally, the monomers are more toxic than other polymers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the synthetic flocculants, polycations primarily account for the fast rise in worldwide consumption. [1][2][3] The chain flexibility, the molecular weight, and the charge density are the main factors determining the application of the cationic polymers in one of the following fields: treatment of drinking water; removal of coal, biological mashes, or waste dyes from industrial wastewaters; paper processing and, related with this, the concentration or thickening of sludges. 4 -8 The combination of polycations with polyanions in dif-ferent ways resulted in a new type of flocculation, dual flocculation.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of polymers for water treatment processes are adopted since 1980 [5]. Cationic polymers are used as primary coagulants, whereas nonionic and anionic polymers are used as coagulant aids mostly [6,7]. The advantages of polymers over mineral coagulants are: more than 50% reduction in sludge volume, lower water content, better dewatering characteristic, no effects on water pH, no increase in total dissolved solids of finished water, no dissolution of any substances in the treated water, which in the case of mineral coagulants the dissolution of Al and Fe happens and shorter settling time [8].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of polymers over mineral coagulants are: more than 50% reduction in sludge volume, lower water content, better dewatering characteristic, no effects on water pH, no increase in total dissolved solids of finished water, no dissolution of any substances in the treated water, which in the case of mineral coagulants the dissolution of Al and Fe happens and shorter settling time [8]. It has been reported that in U.S. more than half of the water treatment plants have employed one or more polyelectrolyte [6]. In some researches, there have been shown that cationic polyelectrolyte are very applicable for the reduction of THM S precursors [9,10].…”
Section: Introductionmentioning
confidence: 99%